2021
DOI: 10.4236/ojts.2021.112007
|View full text |Cite
|
Sign up to set email alerts
|

Bronchotomy as a Safe and Feasible Alternative to Failed Bronchoscopic Removal of Foreign Body Inhalation in Pediatrics. A Seven-Year Review

Abstract: Background: Aspiration of foreign body is popular in pediatric age group and is considered as an important cause of respiratory distress and chocking in these children. Management strategies are different according to the mode of presentation. This study aims to assess the efficacy of rigid bronchoscopy and the role of bronchotomy as a safe alternative for failed removal of inhaled foreign body. Methods: We enrolled 254 patients with foreign body aspiration (FBA) up to 14 years old in a retrospective observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Indications for bronchotomy include the failure to remove the foreign body despite repeated attempts, due to immobility, with or without distal bronchial placement. Elaziz et al have reported on eight cases of thoracotomy and bronchotomy [ 13 ]. They have concluded that bronchotomy is a safe and effective alternative to difficult and failed bronchoscopic extractions [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications for bronchotomy include the failure to remove the foreign body despite repeated attempts, due to immobility, with or without distal bronchial placement. Elaziz et al have reported on eight cases of thoracotomy and bronchotomy [ 13 ]. They have concluded that bronchotomy is a safe and effective alternative to difficult and failed bronchoscopic extractions [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elaziz et al have reported on eight cases of thoracotomy and bronchotomy [ 13 ]. They have concluded that bronchotomy is a safe and effective alternative to difficult and failed bronchoscopic extractions [ 13 ]. In the present case, we performed a bronchotomy, as opposed to a right lower lobectomy, to remove the bronchial foreign body without sacrificing the functioning of the lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Elaziz, M.A., et al [2] have also performed bronchotomy, but their experience was limited to pediatric cases only. Aihole JS et al [3] reported their experience, but it was also limited to pediatric cases only.…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 CTVS Department, AIIMS Rishikesh, Rishikesh 249203, India. 2 Pulmonary Medicine Department, AIIMS Rishikesh, Rishikesh 249203, India.…”
Section: Supplementary Informationmentioning
confidence: 99%